2007
DOI: 10.4269/ajtmh.2007.77.699
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Contamination of Drinking Water within Peri-Urban Households, Lima, Peru

Abstract: We assessed fecal contamination of drinking water in households in 2 peri-urban communities of Lima, Peru. We measured Escherichia coli counts in municipal source water and, within households, water from principal storage containers, stored boiled drinking water, and water in a serving cup. Source water was microbiologically clean, but 26 (28%) of 93 samples of water stored for cooking had fecal contamination. Twenty-seven (30%) of 91 stored boiled drinking water samples grew E. coli. Boiled water was more fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 29 publications
5
71
0
2
Order By: Relevance
“…47 It should also be noted that in these case studies, samples of drinking water were collected from the drinking water vessel. Research has shown that drinking water served in cups is often more contaminated than the corresponding stored drinking water, 45,48 and so our case studies may be overestimating the actual microbiological quality of drinking water in the home. Finally, a major limitation of this study is the reliance on self-reported data to determine consistent HWT use, highlighting the lack of high-quality objective indicators of exclusive HWT use.…”
Section: Discussionmentioning
confidence: 84%
“…47 It should also be noted that in these case studies, samples of drinking water were collected from the drinking water vessel. Research has shown that drinking water served in cups is often more contaminated than the corresponding stored drinking water, 45,48 and so our case studies may be overestimating the actual microbiological quality of drinking water in the home. Finally, a major limitation of this study is the reliance on self-reported data to determine consistent HWT use, highlighting the lack of high-quality objective indicators of exclusive HWT use.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, reported boiling was associated with a significant reduction in contamination of stored water among households with contaminated source water, a finding that is consistent with other research. [31][32][33][34][35][36] In some studies, however, reported boiling has been associated with no effect 37,38 or even an increase in contamination. 39 Because there is no objective measure of boiling, assessment relies on self-report, which may substantially overestimate actual practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although piped water from a municipal source in peri-urban Lima is microbiologically clean, it often becomes fecally contaminated before it is consumed. 34 Variation in antibiotic exposures was sought in Cajamarca, Iquitos, and Chincha by purposively selecting zones and areas within zones along a rural-urban continuum, with allowance for proximity to a fish or chicken farm or health post. In Lima, newer and older slums were selected.…”
Section: Study Sitementioning
confidence: 99%